The Effect of The Brand Image, Advertising and Social Media Marketing on Purchase Decisions - Mafida Zaenati; Luk Luk Atul Hidayati; Marlina Kurnia (Urecol Journal. Part B: Economics and Business, 2022)
This study aims to examine the effect of brand image, advertising and social media marketing on purchasing decisions. The sample of this research is the general public who have purchased a Honda motorcycle consumer in Temanggung regency. The sampling method used quota sampling with a sample size of 100 respondents. The analysis tool used is multiple linear regression with the help of the SPSS version 25.0 program. The result of this study indicates that positive and simultaneously effect on brand image, advertising and social media marketing on purchasing decisions. Partially, brand image and advertising have postive and significantly effect on purchasing decisions, but social media marketing has no effect on purchasing decisions.